Digital Advertising and Influencer Marketing: Effects on Wall's Ice Cream Purchase Intention in Banjarmasin - Aditiyanor; Prihatini Ade Mayvita; Ummi Hanie (Maneggio, 2026)
This study examines the effects of digital advertising and influencer marketing on purchase intention among young consumers of Wall's ice cream in West Banjarmasin, Indonesia. The study adopts a quantitative explanatory design and uses survey data from 100 respondents aged 15–34 years who actively use social media and have been exposed to digital advertising or influencer marketing for Wall's products. Data were collected using a five-point Likert questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that digital advertising has a positive and statistically significant effect on purchase intention (B = 0.475; β = 0.452; p < 0.001). Influencer marketing also has a positive and statistically significant effect (B = 0.496; β = 0.459; p < 0.001). Jointly, the two predictors significantly explain variation in purchase intention (F = 180.149; p < 0.001), with R² = 0.788 and adjusted R² = 0.784. Influencer marketing shows a slightly higher standardized coefficient than digital advertising, although the difference is small and should not be interpreted as a statistically tested difference in effects. The findings suggest that integrated digital advertising and influencer marketing can strengthen consumers' purchase intention by combining message reach with perceived credibility and social influence.